On the stages of distinction of similar grammatical concepts - Garbačiauskienė, M. (Psichologija, 1962)
1. The purpose of this survey was to find out how the process of distinction of grammatical knowledge systems of similar morphological and syntactic word concepts develops. A complex interaction of this knowledge (whose individual traits have both similarities and differences) requires to analyze “the difference inside the sameness” (Engels) and thus helps to identify different stages of development of the most complex form via contrasting distinctive objects. The quality of contrasting (as the substantiation of difference) was the key criterion for determination of the stages of differentiation of similar grammatical knowledge. 2. For that purpose, an individual declarative experiment was carried out with 19 students of the sixth grade and 23 students of the seventh grade. The object of investigation was to examine students’ abilities to distinguish (practically and theoretically): a) a noun and a subject of a sentence; b) a verb and a predicate; c) an adjective and an attribute; d) a part of speech and a part of a sentence. At the beginning students had to mark in the text, for instance, verbs and predicates, then define them and point out their differences. 3. Five stages of differentiation of parts of speech from parts of sentence, characteristic to students, have been established: first, when parts of speech and parts of sentence are considered absolutely identical or just ranged (without any identification in any sense); second, when established similarity and difference are not yet inter-dependable as grammatical categories of gender and voice (similarity is not yet a basis to establish a difference); third, when determination of an outer inessential difference is based on identification of a general feature; fourth, differentiating is made according to the main but not equivalent to parts of speech and parts of sentence, feature; fifth, differentiation through sameness according to essential feature. 4. The fact that the majority of students in VI-VII grades remain in the third and fourth stages can be explained by an unsolved issue in grammar teaching methods regarding contrasted parts of speech and parts of sentence, and the course-book of their the mother tongue does not include the comparison of these grammatical concepts (nor possibilities to compare them).